2017
DOI: 10.1128/jvi.00672-17
|View full text |Cite
|
Sign up to set email alerts
|

A Novel A(H7N2) Influenza Virus Isolated from a Veterinarian Caring for Cats in a New York City Animal Shelter Causes Mild Disease and Transmits Poorly in the Ferret Model

Abstract: In December 2016, a low-pathogenic avian influenza (LPAI) A(H7N2) virus was identified to be the causative source of an outbreak in a cat shelter in New York City, which subsequently spread to multiple shelters in the states of New York and Pennsylvania. One person with occupational exposure to infected cats became infected with the virus, representing the first LPAI H7N2 virus infection in a human in North America since 2003. Considering the close contact that frequently occurs between companion animals and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 72 publications
2
46
0
1
Order By: Relevance
“…Companion animals, such as cats and dogs, have been suggested to be a source of new avian‐origin AIVs, with the potential to cause severe respiratory disease in humans. In 2016, a veterinarian was infected with a low pathogenic avian influenza virus H7N2, which was also isolated from a cat shelter in New York City (Belser et al., ). Canines carrying avian‐origin H3N2 CIV have also the potential to transmit the virus to other species in frequent close contact such as cats (Jeoung et al., ; Park et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Companion animals, such as cats and dogs, have been suggested to be a source of new avian‐origin AIVs, with the potential to cause severe respiratory disease in humans. In 2016, a veterinarian was infected with a low pathogenic avian influenza virus H7N2, which was also isolated from a cat shelter in New York City (Belser et al., ). Canines carrying avian‐origin H3N2 CIV have also the potential to transmit the virus to other species in frequent close contact such as cats (Jeoung et al., ; Park et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Hatta et al assessed transmission of the A/feline/NY/2016 in ferrets and cats. In contrast to Belser et al 1 of 3 pairs of ferrets placed in direct contact showed productive infection and seroconversion but no respiratory droplet transmission to ferrets placed in adjacent cages. They suggested that amino acid differences in the PA, HA, and NA proteins between the human and cat isolates or the small group size may account for this difference.…”
Section: Discussionmentioning
confidence: 64%
“…By measuring particle size, distribution, and infectivity, our study suggests that A(H7N2) transmission had the potential to occur through aerosol transmission of small viral‐laden respiratory droplets and/or contact with viral‐laden fomites. Belser et al investigated the relative risk of transmission among workers using a ferret model of transmission and showed that ferrets intranasally inoculated with the A/NY/108/2016 virus became productively infected but did not transmit the virus to ferrets placed in an adjacent cage. However, naïve ferrets placed in the same cage with infected ferrets showed low‐titer virus in the nasal washes but did not seroconvert.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations